KEARIFAN LOKAL DALAM PEMANFAATAN KAWASAN HUTAN LINDUNG - Abdul Mannan; Muhammad Yusuf; Maddatuang Maddatuang; Sulaiman Zhiddiq; Muhammad Ansarullah S Tabbu; Jeddah Yanti (UNIVERSITAS NEGERI MAKASSAR, 2023)
Deforestation is one of the environmental challenges faced by the global community today, and excessive exploitation of forest resources and land conversion are among the causes of this issue. Utilizing local wisdom to preserve the forest's functions is a significant step toward achieving ecological and economic harmony in forest management in Indonesia. This research aims to unveil the local wisdom of the community in utilizing forest and land resources in the Kalumammang village protected forest area. A combination of qualitative and quantitative descriptive methods is employed in this study, using terrestrial survey data collection, interviews, and geographic information systems. The research results indicate that there are two types of forest resource utilization, namely Logging and Non-Timber Forest Products (NTFPs). There are six objectives for land utilization, which include agriculture, plantations, livestock farming, settlements, public facilities, and village social facilities. Local wisdom with conservation value is evident in the use of forest plants for hunting, determining the age of hunted animals, protecting water sources around livestock farming areas, using organic fertilizers, and implementing agroforestry practices in agricultural and plantation land management.Keyword: Protected Forest, Local Wisdom, Forest and Land Resources